Anti-Imperialism in “Max Havelaar” - Bintang Winarso (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This thesis analyzes how Multatuli shows anti-imperialism through the characters of Max Havelaar and Stern in Max Havelaar. The aim of the thesis is to prove that Max Havelaar and Stern embodies anti-imperialism from their author, Multatuli through their actions, ideas, and commentaries. The analysis of the characters uses theory of imperialism and anti-imperialism. The analysis of the characters is then connected to the real-world perspective of social, culture, and economy that happened around 1850s, by using the theory of new historicism. The results of the analysis show that Max Havelaar and Stern proved their anti-imperialism by fighting against economic, cultural, and political imperialism.